(untitled) (Editora Impacto Científico, 2025)
Supply Networks (SNs) constitute one of the most dynamic and strategic areas of supply chain management, encompassing complex interactions between suppliers, manufacturers, distributors, customers, and institutional actors. Despite the growing relevance of the topic, reviews that synthesize the state of the art and point to directions for future research are still scarce. This article aims to classify, analyze, and discuss the main contributions of the literature on SNs, proposing conceptual and methodological subsidies to guide new studies. The research was conducted through a systematic literature review, based on the Scopus database, which initially resulted in 2,901 publications. From alignment filters, scientific recognition, and full reading, 12 central articles published between 1987 and 2014 were selected. The results reveal that most investigations focus on the relationships of the focal company with upstream suppliers, as well as on structural analyses of the network as a whole, with significant gaps in studies on customers (downstream) and on the interaction of SNs with the external environment. The study also observed an emphasis on themes such as outsourcing, internationalization, knowledge transfer, and mathematical modeling, but still with little exploration of emerging topics such as sustainability, resilience, digitalization, and interorganizational governance. As a contribution, the study organizes the conceptual field of supply chains, highlights gaps, and proposes a research agenda that includes empirical, sectoral, and interdisciplinary approaches. It concludes that the consolidation of the supply chain concept depends on its integration with contemporary challenges, such as Industry 4.0, the circular economy, and cooperation between distinct networks. DOI: https://doi.org/10.56238/edimpacto2025.090-097